Organisasi Sebagai Struktur Sosial - Faruq Abdur Rouf; Nur Arfiyah Febriani (Journal of Innovative and Creativity, 2026)
Organizations are not only understood as administrative entities designed to achieve specific goals but also as social structures that regulate patterns of interaction, roles, hierarchy, and norms that shape the internal dynamics of the organization. From a sociological perspective and in line with Islamic values, organizations are structured systems founded upon principles of equality, justice, and cooperation among their members. This study employs a literature review method to analyze the concept of organizations as social structures, including elements such as hierarchy, roles and responsibilities, communication, and the norms that develop within organizations. The findings indicate that social structure plays a central role in creating order, guiding member behavior, and ensuring organizational effectiveness. In addition, Islamic values provide a moral foundation for maintaining unity, justice, and decision-making processes based on collective benefit (maslahah). The discussion in this article enriches the understanding of the importance of integrating social, structural, and value-based aspects in modern organizational management.